Another side of using load cell to measure the viscosity of a cookie jam for home industries with the ATMega328 for monitoring purposes - Brahmana, Kurnia; Tamba, Takdir (Talenta Publisher, 2019)
A simple structure to measure the viscosity of a cookie jam has been built. The purpose is to help home industries to judge the right time to stop heating and stirring. The value is used in order to get the optimum result of jam for a good taste and economically considered. The load cell is applied to measure the viscosity by fixing it to the stirrer wing and converting the viscosity directly as weight. The number of the viscosity is compared to the OIL SAE commercial standard number and programmed in the microcontroller to display the corresponding values as approximation. The structure and the system can be easily adapted for other kind of purposes with similar interest